THE JAVANESE PALM FLORA, FIRST IMPRESSION - Dransfield, J. (Research Center for Biology-Indonesian Institute of Sciences, 1971)
In comparison with other South East Asian palm floras, the Javanese palm flora is relatively small; there are about 50 species native to the island, With the long history of botanical exploration in Java,and the large concentration of botanists in the island, it would seem surprising if much new remained to be discovered on the island.However, palms are [usually neglected and after my first three months collecting in West Java and working in the Herbarium Bogoriense,it has become obvious that we still know very little of the Taxonomy and natural history of the native Javanese palms.